Single Intramuscular-dose Toxicity of Anti-inflammatory Pharmacopuncture in Rats - Jung Da-jung; Kim Sung-chul; Lee Hyung-geol; Choi Yoo-min; Sin Min-seop; Choi Seok-woo; Song Beom-yong; Kim Jong-uk; Yook Tae-han (Korean Pharmacopuncture Institute, 2013)
Objectives: This study was performed to analyze the toxicity of the test substance, anti-inflammatory pharmacopuncture (AIP), when used as a single intramuscular-dose in 6-week-old, male and female Sprague-Dawley rats and to find the lethal dose. Methods: The experiment was conducted at Biotoxtech according to Good Laboratory Practices. Twenty (20) female and 20 male Spague-Dawley rats were divided into 4 groups of five 5 female and 5 male animals per group. The rats in the three experimental groups received single intramuscular injections with 0.1-㎖, 0.5-㎖ and 1.0-㎖/animal doses of AIP, Groups 2, 3, and 4, respectively, and the control group, Group 1, received a single intramuscular injection with a 1.0-㎖ dose of normal saline. Clinical signs were observed and body weight measurements were carried out for 14 days following the injections. At the end of the observation period, hematology, clinical chemistry, histopathological tests and necropsy were performed on the injected parts. Results: No deaths occurred in any of the groups. Also, histopathological tests showed that AIP had no effect on the injected parts in terms of clinical signs, body weight, hematology, clinical chemistry, and necropsy. Conclusions: As a result of single intramuscular-dose tests of the test substance AIP in 4 groups of rats, the lethal dose for both males and females exceeded 1.0㎖/animal. Therefore, AIP is a relatively safe pharmacopuncture that can be used for treatment, but further studies should be performed.